Identification of Phenolic Compounds in Colored Rice and Their Inhibitory Potential against α-Amylase - Prinya Wongsa (Science Faculty of Chiang Mai University, 2019)
Colored rice varieties (Oryza sativa L.) that are commonly grown and consumed in Thailand were selected for determining and comparing of the contents of phenolic acids and anthocyanins by using an UPLC-ESI-QqQ-MS/MS method with Multiple Reaction Monitoring (MRM) and evaluate their in-vitro evaluate potential inhibitory against a-amylase. A shorten analysis time performed by UPLC-ESI-QqQ-MS/MS was observed. The total phenolic content of crude extract of colored rice samples ranged from 18.2 to 100.0 mg GAE/100 g dried matter (DM). All of 8 target phenolic compounds were detected in polyphenol-rich bound fractions of extracts which were identified and determined. Ferulic acid was the main phenolic acids in all samples while flavonoids including (+)-catechin were significantly observed in red rice sample. In addition, cyanidin-3-glucoside was the most predominant anathocyanins in all colored rice samples. The concentration of cyanidin-3-glucoside ranged from 0.07 mg/100 g DM in the red rice sample to 138.8 mg/100 g DM in the black rice sample. The IC50 value for potential inhibition against a-amylase activity of crude extract of colored rice samples ranged from 2.5 to 14.4 µg/mL. The content of phenolic compounds, total phenolic content and potential inhibition against a-amylase activity in black rice samples were higher than in red and purple rice samples.